The Role of Mnemotechnic Method in Teaching Japanese Language Hieroglyphs (Czech Journal of Multidisciplinary Innovations, 2022)
Today, in the teaching of the Japanese language, special attention is paid to the problem of depicting hieroglyphs in the form of images (with instructions) using computer simulation models based on the mnemonic scheme. The article describes the issues of providing the Japanese language and Japanese hieroglyphs, which are considered important in teaching, to the student through computer and simulation technologies, to make the teaching process more effective and interesting.